'This is our Call of Duty': hegemony, history and resistant videogames in the Middle East. (January 2017) - Saber, Dima; Webber, Nick
In recent years, non-state actors in the Middle East have engaged a new generation of activists through a variety of media strategies. Notable among these is a series of videogame interventions, which have appropriated Western game products to convey political and religious messages through the inversion or complication of the roles of hero and enemy. This article explores a selection of such media, produced by or in support of two non-state groups, Hezbollah and Islamic State (IS). The article takes a discourse theoretical approach to examine the ideologies presented in these media and reflects on the ways in which these game artefacts engage with, and reject, Western narratives of history and of US pre-eminence. It concludes that while these game interventions challenge existing hegemonic (re)presentations of the Middle East and the 'War on Terror', they remove or reduce agency to the extent that those who engage with them can only witness these challenges, rather than instigate their own. While we acknowledge that hegemony can always be challenged, we view this lack of agency as support for Mouffe's proposition that the result of counter-hegemonic resistance is often to maintain and reproduce the hegemonic order.